Reduced graphene oxide/tungsten oxide (rGO/WO3): a versatile nanocomposite for enhanced detection of acetone - Patil, Abhijeet P.; Gaikwad, Mayur A.; Nadargi, Jyoti D.; Shaikh, Hamid; Alam, Mohammad Asif; Tamboli, Mohaseen S.; Kim, Jin Hyeok; Mulla, Imtiaz S.; Suryavanshi, Sharad S. (Journal of Materials Science-Materials In Electronics, 2024)
In this study, we report a straightforward method for synthesizing semi-cubical nanostructures of tungsten trioxide (WO3) loaded with reduced graphene oxide (rGO) via a hydrothermal approach. Furthermore, the systematic investigations were made towards the improved gas sensing capabilities of these nanostructures for acetone. The use of semi-cubical rGO/WO3 nanostructures demonstrate the provision of efficient gas diffusion routes via a meticulously arranged mesoporous framework. Hence, it leads to a significant improvement in the sensing response towards acetone. The analysis of the sensing capabilities demonstrates that the response of the sensor is influenced by variations in operating temperature and gas concentration. It is seen that the inclusion of rGO not only enhances the sensing response but also gives quick response and recovery, which are measured to be 12 and 33 s, respectively. The WO3 sensor loaded with 0.1 wt% rGO demonstrates a discerning reaction to acetone, exhibiting a high response of 93.60% than that of the unmodified WO3 sensor (76.30%). The gas sensing properties are explained through the role of rGO and the structural and morphological properties of the developed nanostructures.

Dual-functional LaFeO3 perovskites via auto-combustion and hydrothermal methods for gas sensing and photocatalytic dye degradation - Patil, Suraj S.; Shinde, Kiran P.; Patil, Abhijeet P.; Abbas, Muhammad Aoun; Nadargi, Jyoti D.; Mujawar, Sarfraj H.; Mulla, Imtiaz S.; Kim, K. B.; Suryavanshi, Sharad S. (Inorganic Chemistry Communications, 2025)
Integrated environmental remediation is increasingly focused on the development of multifunctional materials capable of simultaneous detection of toxic gases and wastewater treatment. Present study aims to develop dual-functional LaFeO3 perovskites for gas sensing and photocatalytic dye degradation. The nanocrystalline powders of LaFeO3 were synthesized via two distinct methods; auto-combustion (A-LFO) and hydrothermal (H-LFO). Numerous characterization techniques (e.g. XRD, SEM, EDAX, BET, TEM, and XPS) were utilized in order to study the phase, morphology, surface area and elemental composition of A-LFO and H-LFO samples. Both samples were systematically evaluated for their potential in the gas sensing and photocatalytic degradation of malachite green (MG). In results, A-LFO exhibited superior performance in both applications, compared to the H-LFO. It shows similar to 90 % sensitivity for the acetone (500 ppm) at the operating temperature of 275 degrees C and achieved similar to 78 % degradation efficiency for malachite green (MG) dye (5 ppm) within 2 h irradiation of natural sunlight. Although, H-LFO presented comparatively lower performance, both materials demonstrated good selectivity, and stability highlighting their promise as a dual-functional environmental remediation agent. By exploring the performance of the synthesized materials in these dual applications, this research established a relationship between synthesis methods, material properties, and overall performance in environmental and industrial applications, by offering a sustainable and efficient solution to complex pollution challenges.
Keywords: Dye degradation; Gas sensing; LaFeO3; Malachite Green; Perovskites

Surfactant-assisted tungsten oxide for enhanced acetone sensing and solar-driven photocatalysis: exploring the role of surfactants - Patil, Abhijeet P.; Patil, Suraj S.; Tamboli, Mohaseen S.; Damkale, Shubhangi R.; Nadargi, Digambar Y.; Nadargi, Jyoti D.; Mulla, Imtiaz S.; Suryavanshi, Sharad S. (RSC Advances, 2025)
Surfactants play a pivotal role in the kinetics of nucleation and accretion of nanoparticles in such a way that they serve as a template for the development of nanostructures, consequently influencing the morphology, dimensions, and other surface properties. Herein, we report the influence of cationic and anionic surfactants (CTAB, SDS, PVP and HMT) on the development of pristine WO3 nanostructures and their impact on gas sensing and photocatalytic properties of WO3. The various surfactant-assisted WO3 nanostructures were synthesized via a straightforward hydrothermal route and systematically analyzed using XRD, FESEM-EDAX, TEM/HRTEM, XPS, UV-Vis, and BET measurements. Gas sensing properties of various oxidizing and reducing gases revealed superior selectivity towards acetone. Among the various surfactant-assisted WO3, CTAB/WO3 exhibited an excellent response of 84.84% towards 100 ppm acetone at an optimal operating temperature of 300 degrees C. The CTAB/WO3 sensor exhibited a linear response to acetone at lower concentrations, showing a 4.8% response at 0.8 ppm, which delineates the threshold between healthy and diabetic breath acetone levels. At 1.8 ppm, the sensor recorded 8.1% response, aligning with diabetes values reported by National Institute for Occupational Safety and Health (NIOSH). Moreover, photocatalytic performance evaluations demonstrated a methylene blue degradation efficiency of 47.19% under natural solar irradiation. This work will motivate researchers in developing high performance acetone gas sensors and photocatalytic dye-degradation by the integration of appropriate surfactants in WO3 nanostructures.